Prevention-based approaches to social policy: The case of early childhood development - Tapper, Alan; Phillimore, John (ANZSOG, 2012)
This article reviews the Australian evidence concerning interventions in early childhood aimed at promoting children’s psychological well-being and preventing social and psychological dysfunction in later life. Two kinds of research are surveyed. One is the Australian social science literature that has emerged in the last twenty years from five major research programs. The other is the evaluation studies that, more recently, have assessed the effectiveness of various early childhood preventive interventions. Together these studies provide an evidentiary platform for reviewing current policy in this field. A full analysis of ‘what works’ would need to include relevant international evidence, which is outside the scope of this article. However, the Australian evidence does support the current policy focus on good parenting programs, while also suggesting that a number of other factors matter in promoting children’s well-being.